Population Variability, Selection Impact and Genotypic Response in Biennial Cycles of Reproductive Stressed Rainfed Rice - Kumar, Prafull; Gupta, A. K.; Kanwar, R. R.; Kumari, Poonam (International Journal of Bio-resource and Stress Management, 2023)
Biennial field experiment (2013−14) was conducted at the S.G. College of Agriculture and Research Station, Jagdalpur; Chhattisgarh, India to study the extent of population variability, impact of selection over them and adaptability to rainfed ecology. After first selection cycle, the retained variability in selection criteria was high and accounted for 20.65 and 17.03% (phenotypic and genotypic) hence further cycle of selection could be practiced for improvement. The maximum phenotypic and genotypic coefficients of variation was observed for crop biomass i.e. biological yield plot-1 (24.27 and 19.57%) followed by grain yield (20.65 and 17.03%) and harvest index (17.75 and 15.67%). The inferior variability coefficients call for addition of newer genotypes and crossing programmes. The estimates of heritability ranged between 44% (panicle length) to 84% (harvest index). Higher magnitude of heritability was recorded for harvest index (84%), spikelet fertility (77%), days to 50% flowering (75%), and crop duration (64%). High estimate of heritability coupled with high genetic advances were observed for harvest index (84% and 29.46, heritability and genetic advance respectively), biological yield plot-1 (56% and 24.47) and grain yield (48% and 21.16). This stumpy intensity of trait transmissibility and genetic gain is owing to unpredictable microenvironment of upland rice. Traits like crop biomass, grain yield and harvest index are concluded critical for rainfed breeding and since possessing high heritability and genetic advance, can be improved by adapting component and direct selection.